Reply: Measurement of hypoxia in the lung in idiopathic pulmonary fibrosis: a matter of control. Issue 3 (10th March 2022) - Porter, Joanna C.; Win, Thida; Erlandsson, Kjell; Thielemans, Kris; Groves, Ashley M.
We thank P-S. Bellaye and co-workers for their considered and insightful response. Given their finding of [ 18 F]fluoromisonidazole ([ 18 F]F-MISO) uptake in the bleomycin mouse model of fibrosis [1], we too were surprised not to demonstrate a similar signal in patients with idiopathic pulmonary fibrosis (IPF). However, as acknowledged, there are other examples of positron emission tomography (PET) tracers, such as cis-4-[ 18 F]-fluoro-l -proline, yielding PET signals in animal lung fibrosis models that have not been replicated in humans with fibrotic lung disease [2, 3]. In vivo PET imaging in IPF patients shows no significant evidence of lung tissue hypoxia https://bit.ly/3fywY7K